An Evaluation of Language Development and Working Memory in Children with Hearing Loss - Dumanlar, Perihan; Akmese, Pelin Pistav; Kirazli, Gulce; Kirazli, Tayfun (Journal of the American Academy of Audiology, 2024)
Background Children with hearing loss (HL) have difficulty in performing the complex functions of language, especially in noisy environments. Cognitive processes such as working memory and short-term memory are effective on individual differences in language skills in children with HL.Purpose The present study aimed to evaluate the vocabulary and syntax skills in language development areas and working memory of children with HL and to compare these results with those of their peers with normal hearing (NH).Research Design In this study, a causal-comparative research model was used to measure vocabulary and syntax skills, which are among the working memory and language development skills of children with NH and those with HL.Study Sample A total of 88 children, 44 children with HL aged 60 to 107 (months) and age- and gender-matched 44 children with NH, were included in the study.Intervention Evaluation was made in two sessions of 20 minutes for each participant.Data Collection and Analysis The language development and working memory of 44 children with HL and 44 children with NH were evaluated and the two groups were compared with each other. The Working Memory Scale (WMS) was used to evaluate the working memory of the participants and three subtests (vocabulary, sentence repetition, and sentence comprehension) of the Test of Language Development-Primary Fourth Edition: Turkish Version (TOLD-P:4) were used to evaluate language development. SPSS 23.0 program was used in the analysis of the data.Results Children with HL obtained lower scores than their peers with NH in all three TOLD-P subtests. Children with HL obtained significantly lower scores in WMS verbal memory and general WMS scores compared with NH children. A positive correlation was found between WMS Verbal Memory Scores and TOLD-P sentence comprehension and sentence repetition scores. WMS Visual Memory Scores predicted the group with HL and all TOLD-P scores and Verbal Memory Scores predicted the group with NH.Conclusion Working memory skills are the predictor of language comprehension, reasoning, learning, literacy skills, and language development. Thus, including working memory skills as well as language skills in the education programs of children with HL contributes to the children's development.
Keywords: hearing loss; cochlear implant; hearing aid; language development; working memory